Release Film

JP7631707B2Active Publication Date: 2025-02-19SUMITOMO BAKELITE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2020141647
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-25
Publication Date
2025-02-19
Estimated Expiration
2040-08-25

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、外観が良好な成形体が得られる離型フィルムが提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631707000009
    Figure 0007631707000009
  • Figure 0007631707000010
    Figure 0007631707000010
  • Figure 0007631707000001
    Figure 0007631707000001
Patent Text Reader

Abstract

To provide a release film capable of obtaining a molded body good in appearance.SOLUTION: When a layer constituting at least one side face is composed of a cured product of a silicone rubber composition, a tear strength of a cured product of the silicone rubber composition measured by the following procedure is TS0 (N / mm), and a breaking elongation is BE0s (%), 2.4×104≤TS0×BE0s is satisfied. (Measurement procedure of tear strength) TS0 is found by creating crescent-shaped test piece using the cured product in accordance with JIS K6252(2001), and measuring a tear strength of the obtained test piece. The unit is N / mm. (Measurement procedure of breaking elongation) A dumbbell-like No.3-type test piece is created using the cured product in accordance with JIS K6251(2004), and the breaking elongation of the obtained test piece is measured. The breaking elongation is calculated by [transfer distance between marked lines (mm)]÷[initial distance between marked lines (20 mm)]×100 to define BE0s. The unit is %.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a release film. [Background technology]

[0002] Conventionally, as a method for manufacturing optical devices, etc., a method has been used in which a release film is disposed in a mold in which a cavity is formed so as to follow the cavity, a curable composition is filled in the cavity, and the curable composition is compression molded in a state in which the support is pressed against the mold so that an optical element provided on the support is inserted into the curable composition in the cavity, thereby integrating the curable composition. As the release film, a fluororesin film, a polyester resin film, and a polyolefin resin film are used (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-245477 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, as a result of the investigations conducted by the present inventors, molded articles obtained using conventional fluororesin films, polyester resin films, and polyolefin resin films as described in the above Patent Document 1 sometimes had distortions at the edges or wrinkles formed on the surface. In other words, it was found that there is room for improvement in terms of obtaining a good appearance of the molded article.

[0005] The above problems also occur with release films used when hardening prepregs of thermosetting resins such as CFRP (carbon fiber reinforced plastics), release films for molding thermosetting resins, and transfer release films for decoration used for printing on products with three-dimensional shapes. [Means for solving the problem]

[0006] The inventors have thoroughly investigated the causes of distortion and wrinkles that occur in molded bodies and have found that when the release layer of a release film has certain physical properties, the release film can conform well to the mold and deformation due to heating and compression can be suppressed, thereby preventing distortion and wrinkles from occurring in the release film. After further investigation, the inventors discovered that by controlling the integrated value of the tear strength and breaking elongation of the release layer, or the degree of change in tear strength before and after heat treatment, as indicators, it is possible to appropriately suppress the occurrence of distortion and wrinkles in the release film and improve the appearance of molded articles using the release film, thereby completing the present invention.

[0007] According to the present invention, A release film in which a layer constituting at least one surface thereof is made of a cured product of a silicone rubber composition, When the tear strength of the cured product of the silicone rubber composition is TS0 (N / mm) and the elongation at break is BE0s (%), as measured by the following procedure, 2.4×10 4 A release film is provided that satisfies ≦TS0×BE0s. (Measuring procedure for tear strength) A crescent-shaped test piece is prepared from the cured product of the silicone rubber composition in accordance with JIS K6252 (2001), and the tear strength of the obtained crescent-shaped test piece at 25°C is measured and taken as TS0 (unit: N / mm). (Procedure for measuring breaking elongation) Using the cured product of the silicone rubber composition, a dumbbell-shaped No. 3 test piece is prepared in accordance with JIS K6251 (2004), and the breaking elongation of the resulting dumbbell-shaped No. 3 test piece is measured at 25°C. The breaking elongation is calculated as [gauge line movement distance (mm)] ÷ [initial gauge line distance (20 mm)] × 100, and is designated as BE0s. The unit is %.

[0008] Further, according to the present invention, When the tear strength of the cured product of the silicone rubber composition, measured by the following procedure, is TS0 (N / mm) and TS1 (N / mm), There is provided a release film in which ((TS1-TS0) / TS0) x 100 is -85% or more and 5% or less. (Measuring procedure for tear strength) A crescent-shaped test specimen is prepared from the cured product of the silicone rubber composition in accordance with JIS K6252 (2001), and the tear strength of the crescent-shaped test specimen obtained at 25°C is designated as TS0 (N / mm). A crescent-shaped test specimen is prepared from the cured product of the silicone rubber composition in accordance with JIS K6252 (2001), and after holding at 100°C for 30 minutes, the tear strength of the crescent-shaped test specimen obtained at 100°C is designated as TS1 (N / mm). Effect of the Invention

[0009] According to the present invention, there is provided a release film which enables a molded article having a good appearance to be obtained. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view that illustrates a cross section of a release film according to a first embodiment; [Diagram 2] FIG. 6 is a cross-sectional view that illustrates a cross section of a release film of a second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. In all drawings, similar components are given the same reference numerals, and explanations are omitted as appropriate. To avoid complexity, (i) when there are multiple identical components in the same drawing, only one of them is given a reference numeral, and not all of them are given a reference numeral, or (ii) especially in Figure 2 and subsequent figures, components similar to those in Figure 1 are not given a reference numeral again. All drawings are for explanatory purposes only. The shapes and dimensional ratios of each member in the drawings do not necessarily correspond to the actual articles.

[0012] In this specification, the expression "a to b" in the explanation of a numerical range means from a to b, unless otherwise specified. For example, "1 to 5% by mass" means "1% by mass to 5% by mass."

[0013] <Indicators of silicone rubber composition> First, the indices of the silicone rubber composition in this embodiment will be described. The silicone rubber composition of the present embodiment is specified by controlling each index, either alone or in combination, which is measured according to the following procedure. In addition, in each index, the cured product of the silicone rubber composition is intended to mean one that has been heated at 160° C. for 20 minutes (first curing) and then post-baked at 200° C. for 4 hours (second curing).

[0014] ·Tear strength TS0 (N / mm) (Measuring procedure for tear strength) A crescent-shaped test piece is prepared from the cured product of the silicone rubber composition in accordance with JIS K6252 (2001), and the tear strength of the obtained crescent-shaped test piece at 25° C. is measured (units are N / mm).

[0015] ·Tear strength TS1 (N / mm) (Measuring procedure for tear strength) A crescent-shaped test piece is prepared in accordance with JIS K6252 (2001) using the cured product of the silicone rubber composition, and then the test piece is held at 100°C for 30 minutes. The tear strength of the crescent-shaped test piece obtained at 100°C is defined as TS1 (N / mm).

[0016] ·Tear strength TS2 (N / mm) (Measuring procedure for tear strength) A crescent-shaped test piece is prepared in accordance with JIS K6252 (2001) using the cured product of the silicone rubber composition, and then the test piece is held at 150°C for 30 minutes. The tear strength of the crescent-shaped test piece obtained at 150°C is defined as TS2 (N / mm).

[0017] Breaking elongation BE0s(%) (Procedure for measuring breaking elongation) Using the cured product of the silicone rubber composition, a dumbbell-shaped No. 3 test piece is prepared in accordance with JIS K6251 (2004), and the breaking elongation of the resulting dumbbell-shaped No. 3 test piece is measured at 25°C. The breaking elongation is calculated as [gauge line movement distance (mm)] ÷ [initial gauge line distance (20 mm)] × 100, and is designated as BE0s. The unit is %.

[0018] Breaking elongation BE0(%) (Procedure for measuring breaking elongation) Using the cured product of the silicone rubber composition, dumbbell-shaped No. 3 test pieces are prepared in accordance with JIS K6251 (2004), and the breaking elongation of the resulting dumbbell-shaped No. 3 test pieces is measured at 25°C. The breaking elongation is calculated as [chuck movement distance (mm)] ÷ [initial chuck distance (60 mm)] × 100, and is designated as BE0. The unit is %.

[0019] Breaking elongation BE1 (%) (Procedure for measuring breaking elongation) Using the cured product of the silicone rubber composition, dumbbell-shaped No. 3 test pieces are prepared in accordance with JIS K6251 (2004), and after holding at 100°C for 30 minutes, the breaking elongation of the resulting dumbbell-shaped No. 3 test pieces is measured at 100°C. The breaking elongation is calculated as [chuck movement distance (mm)] ÷ [initial chuck distance (60 mm)] × 100, and is designated as BE1. The unit is %.

[0020] Breaking elongation BE2 (%) (Procedure for measuring breaking elongation) Using the cured product of the silicone rubber composition, dumbbell-shaped No. 3 test pieces are prepared in accordance with JIS K6251 (2004), and after holding at 150°C for 30 minutes, the breaking elongation of the resulting dumbbell-shaped No. 3 test pieces is measured at 150°C. The breaking elongation is calculated as [chuck movement distance (mm)] ÷ [initial chuck distance (60 mm)] × 100, and is designated as BE2. The unit is %.

[0021] Elongation at 1MPa E1 (%) (Procedure for measuring elongation at 1 MPa) Using the cured product of the silicone rubber composition, dumbbell-shaped No. 3 test pieces are prepared in accordance with JIS K6251 (2004), and a tensile test is carried out at 25°C at a tensile speed of 500 mm / min. The elongation of the obtained dumbbell-shaped No. 3 test piece when the stress reaches 1 MPa is calculated as E1 using the formula [gauge line movement distance (mm)] ÷ [initial gauge line distance (20 mm)] × 100. The unit is %.

[0022] Elongation at 0.2MPa E2 (%) (Procedure for measuring elongation at 0.2 MPa) Using the cured product of the silicone rubber-based curable composition, dumbbell-shaped No. 3 test pieces are prepared in accordance with JIS K6251 (2004), and a tensile test is carried out under conditions of 25°C and a tensile speed of 500 mm / min. When the stress reaches 0.2 MPa, the elongation of the obtained dumbbell-shaped No. 3 test piece is calculated by the formula [gauge line movement distance (mm)] ÷ [initial gauge line distance (20 mm)] × 100. The unit is %.

[0023] Tensile strength S (MPa) (Procedure for measuring tensile strength) A dumbbell-shaped No. 3 test piece is prepared using the cured product of the silicone rubber composition in accordance with JIS K6251 (2004), and the tensile strength of the dumbbell-shaped No. 3 test piece at 25° C. is measured (units are MPa).

[0024] Stroke change rate after n hours SCn(%) (Procedure for measuring stroke change rate) A dumbbell-shaped No. 3 test piece is prepared in accordance with JIS K6251 (2004) using the cured product of the silicone rubber composition, and the elongation of the resulting dumbbell-shaped No. 3 test piece is measured over time at 25°C when held between the chucks at a stress of 1 MPa. The time when the stress becomes 1 MPa is defined as 0h, and the stroke amount after a certain time n (h) is defined as En (%) = [chuck movement distance (mm)] ÷ [initial chuck distance (60 mm)] × 100. The stroke change rate is calculated from the measured stroke amount En based on the following formula. Stroke change rate after n hours SCn (%) = (En-E0) / E0 x 100

[0025] Durometer hardness A (Durometer hardness A measurement procedure) A sheet-like test specimen is prepared using the cured product of the silicone rubber composition, and the durometer hardness A of the resulting sheet-like test specimen at 25° C. is measured in accordance with JIS K6253 (1997).

[0026] Plasticity (Procedure for measuring plasticity) The uncured silicone rubber composition is used as a test sample, and the plasticity of the obtained test sample at 25° C. is measured 10 minutes after the start of the measurement using a Williams plasticity meter in accordance with JIS K6249 (2003).

[0027] The above indexes can be controlled, for example, by appropriately selecting the type and blending amount of each component contained in the silicone rubber composition, the preparation method of the silicone rubber composition, etc. Among these, for example, suitable control of the type and blending ratio of the resin constituting the silicone rubber, the crosslink density and crosslinking structure of the resin, and improving the blending ratio of the inorganic filler and the dispersibility of the inorganic filler are listed as elements for setting the above indexes within the desired numerical range. In addition, by adjusting the temperature and time when the silicone rubber composition is cured, the crosslink density and crosslink structure of the resin can be appropriately controlled, and the above-mentioned indexes can be set to the desired numerical range. In addition, for example, in the production process of the release film, when the film is sandwiched between substrates, it is also possible to change the surface roughness depending on the surface condition.

[0028] First Embodiment FIG. 1 is a cross-sectional view that typically shows a cross section of a release film of the first embodiment. As shown in FIG. 1, a release film 10 of the present embodiment includes a release layer 1, which is made of a silicone rubber composition and satisfies the following conditions. In other words, by using a silicone rubber composition that satisfies specific parameters, a release film 10 having the desired characteristics can be obtained, and the mold conformability and dimensional stability of the molded article using the release film 10 can be improved, making it possible to maintain a good appearance.

[0029] The release film 10 of this embodiment is 2.4×10 4 ≦TS0×BE0s.

[0030] This can prevent the release film 10 from being wrinkled or distorted, and can improve the appearance of the resulting molded article. Although the detailed mechanism is unclear, it is believed that by using the integrated value of tear strength and breaking elongation as an indicator, the balance of rigidity, elastic recovery, extensibility, etc. of the release film 10 can be controlled, and good conformability to the mold can be obtained, thereby effectively suppressing the occurrence of wrinkles and distortion.

[0031] The lower limit of TS0×BE0s is preferably 2.5×10 4 More preferably, 2.8×10 4 This makes it possible to improve mold conformability and dimensional stability, and to stably obtain molded articles with good appearance. On the other hand, the upper limit of TS0×BE0s is not particularly limited, but is, for example, 5.0×10 5 Less than 1.0×10 is acceptable. 5 Less than 9.0×10 is also acceptable. 4 This makes it possible to achieve a good balance of the properties of the release film 10, such as mold followability, dimensional stability, and releasability.

[0032] Alternatively, the release film 10 of the present embodiment is ((TS1-TS0) / TS0) x 100 is greater than or equal to -85% and less than or equal to 5%.

[0033] The inventors focused on the fact that the rubber properties of a cured silicone rubber composition decrease when it is heated, and as a result of their investigations, they discovered that by using the degree of change in the physical properties of the cured silicone rubber composition when heated from room temperature to a high temperature (change in thermal physical properties) as a guideline, it is possible to appropriately control the degree of deformation when heated and the durability of a release film 10 using a cured silicone rubber composition. That is, by controlling the degree of change in tear strength before and after heating, i.e., ((tear strength TS1-tear strength TS0) / tear strength TS0) x 100, within a specific numerical range, it is possible to improve the dimensional stability against heat while maintaining good mold conformability of the release film 10, and to improve the appearance of molded articles using the same. Furthermore, by controlling (tear strength TS1-tear strength TS0) / tear strength TS0) x 100 within a specific numerical range, repeated use of the release film 10 can be expected.

[0034] The upper limit of ((tear strength TS1-tear strength TS0) / tear strength TS0) x 100 is, for example, 5% or less, preferably 0% or less, more preferably -5% or less, and may be -10% or less. On the other hand, the lower limit of the above (tear strength TS1-tear strength TS0) / tear strength TS0)×100 is −85% or more, preferably −70% or more, more preferably −55% or more, and even more preferably −45% or more. By making it equal to or greater than the above lower limit, it is possible to obtain good mold followability, improve dimensional stability in a high temperature environment, and improve mechanical strength. In addition, by making it equal to or greater than the above lower limit, repeated use of the release film 10 can be expected.

[0035] By satisfying the numerical ranges specified by the above-mentioned indicators, the release film of this embodiment can appropriately suppress the occurrence of distortion and wrinkles in the release film and improve the appearance of a molded article using the release film. Furthermore, by satisfying the numerical ranges specified by the following indicators, the occurrence of distortion and wrinkles can be more stably suppressed.

[0036] The release film 10 of this embodiment is 2.8×10 5 It may have the property that TS0×BE0s×S is satisfied. The lower limit of TS0×BE0s×S is 1.4×10 5 More than 2.8×10, preferably 5 More preferably, 3.0×10 5 This makes it possible to improve mold conformability and dimensional stability, and to stably obtain molded articles with good appearance. On the other hand, the upper limit of TS0×BE0s×S is not particularly limited, but is, for example, 6.0×10 6 Less than 2.0×10 is also acceptable. 6 Less than 1.0×10 is acceptable. 6 This makes it possible to achieve a good balance of the properties of the release film 10, such as mold followability, dimensional stability, and releasability.

[0037] The lower limit of the tear strength is, for example, 25 N / mm or more, preferably 28 N / mm or more, more preferably 30 N / mm or more, further preferably 33 N / mm or more, and even more preferably 35 N / mm or more. This can improve the durability of the release film 10. On the other hand, the upper limit of the tear strength is not particularly limited, but may be, for example, 80 N / mm or less, or 70 N / mm or less, which allows a good balance of the properties of the release film 10, such as mold followability, dimensional stability, and releasability.

[0038] The release film 10 of this embodiment is The material may have a characteristic that ((breaking elongation BE1-breaking elongation BE0) / breaking elongation BE0) x 100 satisfies -50% or more and 0% or less.

[0039] In addition, the release film 10 of this embodiment is The material may have a characteristic that ((breaking elongation BE2-breaking elongation BE0) / breaking elongation BE0) x 100 satisfies -65% or more and 0% or less.

[0040] The upper limit of ((breaking elongation BE2-breaking elongation BE0) / breaking elongation BE0) x 100 is not particularly limited, but may be, for example, 0% or less, preferably -20% or less, and more preferably -30% or less. On the other hand, the lower limit of the above ((breaking elongation BE2-breaking elongation BE0) / breaking elongation BE0) x 100 is, for example, -65% or more, preferably -60% or more, and more preferably -55% or more. This makes it possible to suppress changes in dimensional stability and durability in a high-temperature environment.

[0041] The upper limit of the breaking elongation BE1 may be, for example, 1500% or less, preferably 1200% or less, more preferably 1000% or less, and further preferably 900% or less, whereby the mechanical strength of the release film 10 can be improved. On the other hand, the lower limit of the breaking elongation BE1 is 250% or more, preferably 300% or more, and more preferably 350% or more, which can suppress changes in dimensional stability and durability in a high-temperature environment.

[0042] The release film 10 of this embodiment is The characteristic may be such that ((TS2-TS0) / TS0) x 100 is equal to or greater than -88% and equal to or less than 5%.

[0043] The upper limit value of ((tear strength TS2-tear strength TS0) / tear strength TS0) x 100 is, for example, 5% or less, preferably 0% or less, and may be -20% or less, or further -30% or less. On the other hand, the lower limit of the above (tear strength TS2-tear strength TS0) / tear strength TS0) x 100 is -88% or more, preferably -70% or more, more preferably -60% or more, and even more preferably -50% or more. By making it equal to or more than the above lower limit, the dimensional stability against heat can be improved while maintaining good mold followability of the release film 10, and the appearance of the molded article using this can be improved.

[0044] The upper limit of the tear strength TS1 is not particularly limited, but may be, for example, 60 N / mm or less, 50 N / mm or less, or 40 N / mm or less. On the other hand, the lower limit of the tear strength TS1 is, for example, 10 N / mm or more, preferably 20 N / mm or more, more preferably 25 N / mm or more, and even more preferably 30 N / mm or more.

[0045] The upper limit of the tear strength TS2 is not particularly limited, but may be, for example, 50 N / mm or less, 40 N / mm or less, or 35 N / mm or less, which allows for a good balance with other physical properties. On the other hand, the lower limit of the tear strength TS2 is, for example, 6.5 N / mm or more, preferably 10 N / mm or more, more preferably 15 N / mm or more, which improves the dimensional stability against heat while maintaining good mold conformability of the release film 10, and can improve the appearance of a molded article using the same.

[0046] The release film 10 of this embodiment is It may have the characteristics of satisfying 15≦E1 and 20≦TS0.

[0047] That is, by using the elongation under low stress (E1) and tear strength (TS0) as indicators and controlling them simultaneously, a good balance between mold conformability and dimensional stability can be stably obtained.

[0048] The lower limit of E1 is at least 15, preferably at least 30, and more preferably at least 50. This increases the ease of deformation, and more stably maintains mold followability and dimensional stability, resulting in a molded product with good appearance. On the other hand, the upper limit of E1 is not particularly limited, but may be, for example, 500 or less, 400 or less, 300 or less, or, depending on the purpose, 100 or less. This allows a good balance of the properties of the release film 10, such as mold followability, dimensional stability, and releasability.

[0049] The release film 10 of this embodiment is E1 and E2 may have the property that 10≦|E1−E2| is satisfied.

[0050] The lower limit of |E1-E2| is at least 10, preferably at least 20, and more preferably at least 30. This makes it easier to improve mold followability and dimensional stability. On the other hand, the upper limit of |E1-E2| is not particularly limited, but may be, for example, 500 or less, 400 or less, 300 or less, or, depending on the purpose, 90 or less. This allows the properties of the release film 10, such as mold followability, dimensional stability, and releasability, to be well balanced.

[0051] According to the study by the present inventors, the elongation amount (E1) at low stress and the tear strength (TS0) are in a trade-off relationship, that is, when the amount of filler in the silicone rubber is reduced, the elongation amount at low stress can be increased, but on the other hand, the tear strength decreases and the durability of the silicone rubber decreases. As a result of further intensive study, it was found that by appropriately selecting the components of the silicone rubber composition, such as the vinyl group-containing organopolysiloxane described below, it is possible to control the uneven distribution of crosslink density and crosslinked structure, and to increase the elongation amount at low stress in a wide strain range while increasing the tear strength of the cured product of the silicone rubber composition. Although the detailed mechanism is unclear, it is considered that the crosslinking state can be appropriately controlled by using two different types of vinyl group-containing organopolysiloxanes in combination or by using a low vinyl group organopolysiloxane, so that the tear strength of the cured product of the silicone rubber composition can be increased while improving the elongation amount at stress.

[0052] The release film 10 of this embodiment is When the stroke change rate after 1 hour of the cured silicone rubber-based curable resin composition is defined as SC1 (%), It may have the characteristics that satisfy SC1≦50 and 20≦TS0.

[0053] In other words, by using the initial stroke change rate and tear strength as indicators and controlling them simultaneously, a good balance of mechanical strength, durability, mold conformability, and dimensional stability can be stably obtained.

[0054] The upper limit of SC1 may be not more than 50, preferably not more than 40, and more preferably not more than 30. This makes it possible to more stably maintain mold followability and dimensional stability, and to obtain a molded article having a good appearance. On the other hand, the lower limit of SC1 is not particularly limited, but may be equal to or greater than 1, or may be equal to or greater than 2. This makes it possible to improve the mechanical strength while achieving a good balance between the properties of the release film 10, such as mold followability and dimensional stability.

[0055] Furthermore, when the stroke change rate after 5 hours is defined as SC5 (%), the upper limit of SC5 may be 70 or less, preferably 50 or less, and more preferably 40 or less. This makes it possible to obtain a molded product having good durability, mold followability and dimensional stability, and a good appearance. On the other hand, the lower limit of SC5 is not particularly limited, but may be equal to or greater than 1, or may be equal to or greater than 3. This makes it possible to improve the mechanical strength while achieving a good balance between the properties of the release film 10, such as mold followability and dimensional stability.

[0056] The release film 10 of this embodiment is It may have the property that |SC5-SC1|≦20 is satisfied.

[0057] The upper limit of |SC5-SC1| may be equal to or less than 20, preferably equal to or less than 15, and more preferably equal to or less than 10. This makes it easier to improve durability and more stably maintain mold followability and dimensional stability. On the other hand, the lower limit of |SC5-SC1| is not particularly limited, but may be equal to or greater than 1. This makes it possible to realize a silicone rubber composition that is well balanced with other properties.

[0058] The lower limit of the tear strength TS0 is, for example, 25 N / mm or more, preferably 28 N / mm or more, more preferably 30 N / mm or more, even more preferably 33 N / mm or more, and still more preferably 35 N / mm or more, which can improve the durability of the release film 10 during repeated use. On the other hand, the upper limit of the tear strength TS0 is not particularly limited, but may be, for example, 80 N / mm or less, or 70 N / mm or less. While maintaining mechanical strength, the properties of the release film 10, such as mold followability and dimensional stability, can be well balanced.

[0059] The upper limit of the durometer hardness A of the cured product of the silicone rubber composition of the present embodiment is not particularly limited, but may be, for example, not more than 80, preferably not more than 65, and more preferably not more than 60. This improves the curability of the silicone rubber composition, enhances the deformability that makes it easy to deform, and improves the mold followability and dimensional stability. On the other hand, the lower limit of the durometer hardness A is not particularly limited, but is, for example, not less than 20, preferably not less than 25, and more preferably not less than 30. This makes it possible to increase the mechanical strength of the release film 10.

[0060] The lower limit of the plasticity of the silicone rubber composition is, for example, not less than 80, preferably not less than 90, and more preferably not less than 100. This can enhance the stability during film formation using the silicone rubber composition. On the other hand, the upper limit of the plasticity of the silicone rubber composition is, for example, not more than 340, preferably not more than 320, and more preferably not more than 300. This can improve the stability during film formation.

[0061] The release film 10 of this embodiment has a surface free energy of 10 mJ / m 2 More than 20mJ / m 2 It is preferable that: By adjusting the surface free energy to be equal to or higher than the above lower limit, good releasability can be achieved.

[0062] In this embodiment, it is preferable that at least one surface of the release film 10 has the above surface free energy, and it is more preferable that the release surface 3 has the above surface free energy. In addition, both the release surface 3 and the surface opposite to the release surface 3 may have the above surface free energy.

[0063] The surface free energy can be measured using a general-purpose contact angle meter (for example, Drop Master DM-501, a contact angle meter manufactured by Kyowa Interface Science Co., Ltd.). Specifically, water, diiodomethane, and hexadecane are used as three types of liquids whose surface free energy and each of its components (dispersion force, polar force, and hydrogen bonding force) are known, and the contact angle (θ) of each liquid on the release layer 11 is measured using a contact angle meter at 23°C and 65% RH. From this contact angle (θ) value and the known values ​​of each liquid (the values ​​obtained from Panzer's Method IV (described in the Journal of the Japan Adhesion Association, Vol. 15, No. 3, p. 96)), the values ​​of each component are calculated using the following formula, which is derived from the Kitazaki-Hata formula. (γSd·γLd)1 / 2+(γSp·γLp)1 / 2+(γSh·γLh)1 / 2=γL(1+cosθ) / 2 Here, γLd, γLp, and γLh respectively represent the components of dispersion force, polar force, and hydrogen bonding force of the measurement liquid. θ represents the contact angle of the measurement liquid on the measurement surface. γSd, γSp, and γSh respectively represent the values ​​of the components of dispersion force, polar force, and hydrogen bonding force of the release layer surface. γL represents the surface energy of each liquid. The values ​​of the three components of the measurement surface (release layer surface) are determined by solving the simultaneous equations obtained by substituting the known values ​​and θ into the above formula. Then, the sum of the determined dispersion force component value, polar force component value, and hydrogen bonding force component value can be calculated as the surface free energy (E) using the following formula. E = γSd + γSp + γSh

[0064] The release film 10 of this embodiment is composed of a release layer 1. The release layer 1 will be described below.

[0065] [Release layer] The release surface 3 of the release layer 1 is the surface that comes into contact with a sealing resin, which will be described later, when the release film 10 is used. The surface roughness Rz of the release surface 3 is 0.1 to 10 μm, preferably 1 to 7 μm, and more preferably 1 to 5 μm. By setting the surface roughness Rz of the release surface 3 to be equal to or greater than the above lower limit, a good balance between releasability and mold conformability during molding can be achieved. On the other hand, by setting the surface roughness Rz of the release surface 3 to be equal to or less than the above upper limit, good releasability can be achieved while maintaining mold conformability and dimensional stability.

[0066] The surface roughness of the release surface 3 can be controlled by known methods, such as transferring an embossed pattern to the film using an embossed roll during the production process of the release film, or by incorporating particles into the material of the release layer.

[0067] The surface roughness Rz of the release layer 1 is measured in accordance with JIS B0601:2013.

[0068] The thickness of the release layer 1 is preferably 30 μm or more and 500 μm or less, more preferably 100 μm or more and 400 μm or less, and even more preferably 150 μm or more and 300 μm or less. By setting the thickness of the release layer 1 to the above lower limit or more, the rigidity of the release film 10 is increased, and excessive deformation and wrinkles are easily suppressed. As a result, mold followability and dimensional stability are obtained. On the other hand, by setting the thickness of the release layer 1 to the above upper limit or less, the rigidity of the release film 10 can be controlled, and a good balance between mold followability and releasability can be achieved.

[0069] The release layer 1 is made of a silicone rubber composition. In this embodiment, the silicone rubber composition is a rubber material having rubber-like properties such as elasticity, compressibility, etc., of silicone having a siloxane bond (-Si-O-Si-) as the main skeleton. The present inventors focused on a release film as a new application of the silicone rubber composition, and realized a new release film using the silicone rubber composition. The silicone rubber composition of this embodiment will now be described.

[0070] <<Vinyl group-containing organopolysiloxane (A)>> The silicone rubber composition of the present embodiment may contain a vinyl group-containing organopolysiloxane (A). The vinyl group-containing organopolysiloxane (A) is a polymer that is the main component of the silicone rubber composition.

[0071] The vinyl group-containing organopolysiloxane (A) can contain a vinyl group-containing linear organopolysiloxane (A1) having a linear structure.

[0072] The vinyl group-containing linear organopolysiloxane (A1) has a linear structure and contains vinyl groups, and these vinyl groups become crosslinking points during curing.

[0073] The vinyl group content of the vinyl group-containing linear organopolysiloxane (A1) is not particularly limited, but for example, it is preferable that the vinyl group content is 15 mol% or less and that the vinyl group content is 2 or more in the molecule. This optimizes the amount of vinyl groups in the vinyl group-containing linear organopolysiloxane (A1), and ensures the formation of a network with each component described below.

[0074] In this specification, the vinyl group content refers to the mol % of vinyl group-containing siloxane units when all units constituting the vinyl group-containing linear organopolysiloxane (A1) are taken as 100 mol %, where it is considered that there is one vinyl group per vinyl group-containing siloxane unit.

[0075] The degree of polymerization of the vinyl group-containing linear organopolysiloxane (A1) is not particularly limited, but is, for example, preferably within the range of about 1000 to 10000, and more preferably about 2000 to 5000. The degree of polymerization can be determined, for example, as the polystyrene-equivalent number average degree of polymerization (or number average molecular weight) measured by GPC (gel permeation chromatography) using chloroform as a developing solvent.

[0076] Furthermore, the specific gravity of the vinyl group-containing linear organopolysiloxane (A1) is not particularly limited, but is preferably in the range of about 0.9 to 1.1.

[0077] By using a vinyl group-containing linear organopolysiloxane (A1) having a degree of polymerization and specific gravity within the above ranges, it is possible to improve the heat resistance, flame retardancy, chemical stability, etc. of the resulting silicone rubber.

[0078] The vinyl group-containing linear organopolysiloxane (A1) preferably has a structure represented by the following formula (1).

[0079] [ka]

[0080] In formula (1), R 1 is a substituted or unsubstituted alkyl group, alkenyl group, aryl group, or a hydrocarbon group consisting of a combination thereof, each having 1 to 10 carbon atoms. Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, and a propyl group, with a methyl group being preferred. Examples of the alkenyl group having 1 to 10 carbon atoms include a vinyl group, an allyl group, and a butenyl group, with a vinyl group being preferred. Examples of the aryl group having 1 to 10 carbon atoms include a phenyl group.

[0081] Also, R 2 is a substituted or unsubstituted alkyl group, alkenyl group, aryl group, or a hydrocarbon group consisting of a combination thereof, each having 1 to 10 carbon atoms. Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, and a propyl group, and among these, a methyl group is preferable. Examples of the alkenyl group having 1 to 10 carbon atoms include a vinyl group, an allyl group, and a butenyl group. Examples of the aryl group having 1 to 10 carbon atoms include a phenyl group.

[0082] Also, R 3is a substituted or unsubstituted alkyl group having 1 to 8 carbon atoms, an aryl group, or a hydrocarbon group consisting of a combination thereof. Examples of the alkyl group having 1 to 8 carbon atoms include a methyl group, an ethyl group, and a propyl group, and among these, a methyl group is preferable. Examples of the aryl group having 1 to 8 carbon atoms include a phenyl group.

[0083] Furthermore, R in formula (1) 1 and R 2 Examples of the substituent of R include a methyl group and a vinyl group. 3 Examples of the substituent include a methyl group.

[0084] In addition, in formula (1), multiple R 1 are independent of each other and may be different or the same. 2 , and R 3 The same applies to.

[0085] Furthermore, m and n are the numbers of repeating units constituting the vinyl group-containing linear organopolysiloxane (A1) represented by formula (1), where m is an integer of 0 to 2000 and n is an integer of 1000 to 10000. m is preferably 0 to 1000 and n is preferably 2000 to 5000.

[0086] A specific example of the structure of the vinyl group-containing linear organopolysiloxane (A1) represented by formula (1) is that represented by the following formula (1-1).

[0087] [ka]

[0088] In formula (1-1), R 1 and R 2 are each independently a methyl group or a vinyl group, and at least one of them is a vinyl group.

[0089] The vinyl group-containing linear organopolysiloxane (A1) may contain a first vinyl group-containing linear organopolysiloxane (A1-1) having two or more vinyl groups in the molecule and having a vinyl group content of 0.4 mol% or less. The vinyl group content of the first vinyl group-containing linear organopolysiloxane (A1-1) may be 0.1 mol% or less.

[0090] The vinyl group-containing linear organopolysiloxane (A1) may contain a first vinyl group-containing linear organopolysiloxane (A1-1) and a second vinyl group-containing linear organopolysiloxane (A1-2) having a vinyl group content of 0.5 to 15 mol %.

[0091] By combining the first vinyl group-containing linear organopolysiloxane (A1-1) and the second vinyl group-containing linear organopolysiloxane (A1-2) with a high vinyl group content as the raw rubber, which is the raw material of the silicone rubber, the vinyl groups can be unevenly distributed, and the crosslinking density can be more effectively formed in the crosslinking network of the silicone rubber. As a result, the tear strength of the cured product of the silicone rubber composition can be more effectively increased, and the dimensional stability and transferability can be easily controlled.

[0092] Specifically, the vinyl group-containing linear organopolysiloxane (A1) may be, for example, a vinyl group-containing linear organopolysiloxane represented by the above formula (1-1), 1 is a vinyl group and / or R 2 a first vinyl group-containing linear organopolysiloxane (A1-1) having two or more units in the molecule each of which is a vinyl group and containing 0.4 mol % or less of a unit represented by R 1 is a vinyl group and / or R 2 It is preferable to use a second vinyl group-containing linear organopolysiloxane (A1-2) containing 0.5 to 15 mol % of units in which the vinyl group is present.

[0093] The first vinyl group-containing linear organopolysiloxane (A1-1) preferably has a vinyl group content of 0.01 to 0.2 mol %, and the second vinyl group-containing linear organopolysiloxane (A1-2) preferably has a vinyl group content of 0.8 to 12 mol %.

[0094] Furthermore, when the first vinyl group-containing linear organopolysiloxane (A1-1) and the second vinyl group-containing linear organopolysiloxane (A1-2) are combined and blended, the ratio of (A1-1) to (A1-2) is not particularly limited, but for example, the weight ratio of (A1-1):(A1-2) is preferably 50:50 to 95:5, and more preferably 80:20 to 90:10.

[0095] The first and second vinyl group-containing linear organopolysiloxanes (A1-1) and (A1-2) may each be used alone or in combination of two or more.

[0096] The vinyl group-containing organopolysiloxane (A) may also contain a vinyl group-containing branched organopolysiloxane (A2) having a branched structure.

[0097] <<Organohydrogenpolysiloxane (B)>> The silicone rubber composition of the present embodiment can contain an organohydrogenpolysiloxane (B). The organohydrogenpolysiloxane (B) is classified into a linear organohydrogenpolysiloxane (B1) having a linear structure and a branched organohydrogenpolysiloxane (B2) having a branched structure, and may contain either one or both of these.

[0098] The linear organohydrogenpolysiloxane (B1) has a linear structure and a structure in which hydrogen is directly bonded to Si (≡Si-H), and is a polymer that undergoes a hydrosilylation reaction with the vinyl groups of the vinyl group-containing organopolysiloxane (A) and with vinyl groups of the components blended into the silicone rubber composition, thereby crosslinking these components.

[0099] The molecular weight of the linear organohydrogenpolysiloxane (B1) is not particularly limited, but for example, the weight average molecular weight is preferably 20,000 or less, and more preferably 1,000 or more and 10,000 or less.

[0100] The weight average molecular weight of the linear organohydrogenpolysiloxane (B1) can be measured, for example, by polystyrene conversion in gel permeation chromatography (GPC) using chloroform as a developing solvent.

[0101] Furthermore, it is usually preferred that the linear organohydrogenpolysiloxane (B1) does not have a vinyl group, which can reliably prevent the crosslinking reaction from proceeding within the molecule of the linear organohydrogenpolysiloxane (B1).

[0102] As the linear organohydrogenpolysiloxane (B1) as described above, for example, one having a structure represented by the following formula (2) is preferably used.

[0103] [ka]

[0104] In formula (2), R 4is a substituted or unsubstituted alkyl group, alkenyl group, aryl group, a hydrocarbon group combining these groups, or a hydride group having 1 to 10 carbon atoms. Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, a propyl group, etc., and among these, a methyl group is preferable. Examples of the alkenyl group having 1 to 10 carbon atoms include a vinyl group, an allyl group, a butenyl group, etc. Examples of the aryl group having 1 to 10 carbon atoms include a phenyl group.

[0105] Also, R 5 is a substituted or unsubstituted alkyl group, alkenyl group, aryl group, a hydrocarbon group combining these groups, or a hydride group having 1 to 10 carbon atoms. Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, and a propyl group, and among these, a methyl group is preferable. Examples of the alkenyl group having 1 to 10 carbon atoms include a vinyl group, an allyl group, and a butenyl group. Examples of the aryl group having 1 to 10 carbon atoms include a phenyl group.

[0106] In addition, in formula (2), multiple R 4 are independent of each other and may be different or the same. 5 The same applies to R. 4 and R 5 At least two of these are hydride groups.

[0107] Also, R 6 is a substituted or unsubstituted alkyl group having 1 to 8 carbon atoms, an aryl group, or a hydrocarbon group combining these. Examples of the alkyl group having 1 to 8 carbon atoms include a methyl group, an ethyl group, and a propyl group, and among these, a methyl group is preferable. Examples of the aryl group having 1 to 8 carbon atoms include a phenyl group. 6 are independent of each other and may be different from each other or may be the same.

[0108] In addition, R in formula (2) 4 ,R 5 ,R 6Examples of the substituent include a methyl group and a vinyl group, and from the viewpoint of preventing an intramolecular crosslinking reaction, a methyl group is preferred.

[0109] Furthermore, m and n are the numbers of repeating units constituting the linear organohydrogenpolysiloxane (B1) represented by formula (2), where m is an integer of 2 to 150 and n is an integer of 2 to 150. Preferably, m is an integer of 2 to 100 and n is an integer of 2 to 100.

[0110] The linear organohydrogenpolysiloxane (B1) may be used alone or in combination of two or more kinds.

[0111] Since the branched organohydrogenpolysiloxane (B2) has a branched structure, it forms regions with high crosslink density, and is a component that greatly contributes to the formation of a sparsely-dense structure of crosslink density in the silicone rubber system. Also, like the linear organohydrogenpolysiloxane (B1), it has a structure in which hydrogen is directly bonded to Si (≡Si-H), and is a polymer that undergoes a hydrosilylation reaction with the vinyl groups of the vinyl group-containing organopolysiloxane (A) and the vinyl groups of the components blended in the silicone rubber composition, thereby crosslinking these components.

[0112] The specific gravity of the branched organohydrogenpolysiloxane (B2) is in the range of 0.9 to 0.95.

[0113] Furthermore, it is usually preferred that the branched organohydrogenpolysiloxane (B2) does not have a vinyl group, which can reliably prevent the crosslinking reaction from proceeding within the molecule of the branched organohydrogenpolysiloxane (B2).

[0114] As the branched organohydrogenpolysiloxane (B2), one represented by the following average composition formula (c) is preferred.

[0115] Average composition formula (c) (H a (R7 ) 3-a SiO 1 / 2 ) m (SiO 4 / 2 ) n (In formula (c), R 7 is a monovalent organic group, a is an integer ranging from 1 to 3, and m is H a (R 7 ) 3-a SiO 1 / 2 The number of units, n, is SiO 4 / 2 (the number of units)

[0116] In formula (c), R 7 is a monovalent organic group, preferably a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, an aryl group, or a hydrocarbon group consisting of a combination thereof. Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, and a propyl group, and among these, a methyl group is preferred. Examples of the aryl group having 1 to 10 carbon atoms include a phenyl group.

[0117] In formula (c), a is the number of hydride groups (hydrogen atoms directly bonded to Si) and is an integer ranging from 1 to 3, and preferably 1.

[0118] In addition, in formula (c), m is H a (R 7 ) 3-a SiO 1 / 2 The number of units, n, is SiO 4 / 2 It is the number of units.

[0119] The branched organohydrogenpolysiloxane (B2) has a branched structure. The linear organohydrogenpolysiloxane (B1) and the branched organohydrogenpolysiloxane (B2) differ in that their structures are linear or branched, and the number of alkyl groups R bonded to Si (R / Si) when the number of Si is 1 is in the range of 1.8 to 2.1 for the linear organohydrogenpolysiloxane (B1) and 0.8 to 1.7 for the branched organohydrogenpolysiloxane (B2).

[0120] Since the branched organohydrogenpolysiloxane (B2) has a branched structure, for example, when heated in a nitrogen atmosphere to 1000° C. at a heating rate of 10° C. / min, the amount of residue is 5% or more. In contrast, since the linear organohydrogenpolysiloxane (B1) is linear, the amount of residue after heating under the above conditions is almost zero.

[0121] Specific examples of the branched organohydrogenpolysiloxane (B2) include those having a structure represented by the following formula (3).

[0122] [ka]

[0123] In formula (3), R 7 R is a substituted or unsubstituted alkyl group having 1 to 8 carbon atoms, an aryl group, or a hydrocarbon group combining these, or a hydrogen atom. Examples of the alkyl group having 1 to 8 carbon atoms include a methyl group, an ethyl group, and a propyl group, and among these, a methyl group is preferable. Examples of the aryl group having 1 to 8 carbon atoms include a phenyl group. 7 Examples of the substituent include a methyl group.

[0124] In addition, in formula (3), multiple R 7 are independent of each other and may be different from each other or may be the same.

[0125] In addition, in formula (3), "-O-Si≡" indicates that Si has a branched structure extending three-dimensionally.

[0126] The branched organohydrogenpolysiloxane (B2) may be used alone or in combination of two or more kinds.

[0127] In addition, the amount of hydrogen atoms (hydride groups) directly bonded to Si in the linear organohydrogenpolysiloxane (B1) and the branched organohydrogenpolysiloxane (B2) is not particularly limited. However, in the silicone rubber composition, the total amount of hydride groups in the linear organohydrogenpolysiloxane (B1) and the branched organohydrogenpolysiloxane (B2) is preferably 0.5 to 5 moles, more preferably 1 to 3.5 moles, per mole of vinyl group in the vinyl group-containing linear organopolysiloxane (A1). This ensures that a crosslinked network is formed between the linear organohydrogenpolysiloxane (B1) and the branched organohydrogenpolysiloxane (B2) and the vinyl group-containing linear organopolysiloxane (A1).

[0128] <<Inorganic particles (C)>> The silicone rubber composition of the present embodiment is a vinyl group-containing Yes Lugano Poly In addition to the siloxane (A), inorganic particles (C) may be contained.

[0129] The inorganic particles (C) are not particularly limited, but may be particles made of one or more selected from the group consisting of diatomaceous earth, iron oxide, titanium oxide, barium oxide, magnesium oxide, cerium oxide, magnesium carbonate, zinc carbonate, glass wool, mica, calcium carbonate, zinc oxide, alumina, crystalline silica, amorphous silica, fused silica, and zeolite. Among these, one or more selected from the group consisting of calcium carbonate, zinc oxide, alumina, crystalline silica, amorphous silica, fused silica, and zeolite are preferred. Furthermore, depending on the synthesis method of silica, fumed silica (flame-processed silica), fired silica, precipitated silica, and the like may be used. The inorganic particles (C) may be used alone or in combination of two or more kinds.

[0130] The inorganic particles (C) have a specific surface area, as measured by the BET method, of, for example, 50 to 400 m 2 / g, and 100 to 400m 2 It is more preferable that the molecular weight is / g. The average primary particle size of the inorganic particles (C) is, for example, preferably from 1 to 100 nm, and more preferably from about 5 to 20 nm.

[0131] By using inorganic particles (C) having a specific surface area and average particle size within this range, the hardness and mechanical strength of the formed release layer 1 can be improved, and the balance between releasability, mold conformability, and dimensional stability can be improved.

[0132] <<Silane coupling agent (D)>> The silicone rubber composition of this embodiment may contain a silane coupling agent (D). The silane coupling agent (D) may have a hydrolyzable group. The hydrolyzable group is hydrolyzed by water to become a hydroxyl group, and the hydroxyl group undergoes a dehydration condensation reaction with the hydroxyl group on the surface of the inorganic particles (C), thereby modifying the surface of the inorganic particles (C).

[0133] In addition, the silane coupling agent (D) may contain a silane coupling agent having a hydrophobic group. This provides the surface of the inorganic particles (C) with this hydrophobic group, which reduces the cohesive force of the inorganic particles (C) in the silicone rubber composition and thus in the silicone rubber (in the case of silica particles, the cohesion caused by hydrogen bonds due to silanol groups is reduced), and as a result, it is presumed that the dispersibility of the inorganic particles (C) in the silicone rubber composition is improved. This increases the interface between the inorganic particles (C) and the rubber matrix, and enhances the reinforcing effect of the inorganic particles (C). Furthermore, it is presumed that the slipperiness of the inorganic particles (C) in the matrix is ​​improved during deformation of the rubber matrix. And, due to the improvement in the dispersibility and slipperiness of the inorganic particles (C), the mechanical strength (for example, mold followability, dimensional stability, etc.) of the release layer 1 due to the inorganic particles (C) is improved.

[0134] Furthermore, the silane coupling agent (D) may contain a silane coupling agent having a vinyl group. This allows the vinyl group to be introduced onto the surface of the inorganic particles (C). Therefore, when the silicone rubber composition is cured, that is, when the vinyl group of the vinyl group-containing organopolysiloxane (A) and the hydride group of the organohydrogenpolysiloxane (B) undergo a hydrosilylation reaction to form a network (crosslinked structure), the vinyl group of the inorganic particles (C) (in the case of silica particles) also participates in the hydrosilylation reaction with the hydride group of the organohydrogenpolysiloxane (B), so that the inorganic particles (C) are also incorporated into the network. This allows the release layer 1 to be formed with a low hardness and a high modulus.

[0135] As the silane coupling agent (D), a silane coupling agent having a hydrophobic group and a silane coupling agent having a vinyl group can be used in combination.

[0136] An example of the silane coupling agent (D) is one represented by the following formula (4).

[0137] Y n -Si-(X) 4-n (4) In the above formula (4), n represents an integer of 1 to 3. Y represents any functional group having a hydrophobic group, a hydrophilic group, or a vinyl group, and when n is 1, it is a hydrophobic group, and when n is 2 or 3, at least one of them is a hydrophobic group. X represents a hydrolyzable group.

[0138] The hydrophobic group is an alkyl group having 1 to 6 carbon atoms, an aryl group, or a hydrocarbon group formed by combining these groups. Examples of the hydrophobic group include a methyl group, an ethyl group, a propyl group, and a phenyl group, and among these, a methyl group is preferable.

[0139] Examples of the hydrophilic group include a hydroxyl group, a sulfonic acid group, a carboxyl group, and a carbonyl group, and among these, a hydroxyl group is preferred. The hydrophilic group may be included as a functional group, but it is preferred that the hydrophilic group is not included from the viewpoint of imparting hydrophobicity to the silane coupling agent (D).

[0140] Further, examples of the hydrolyzable group include alkoxy groups such as methoxy and ethoxy groups, chloro groups, and silazane groups. Among these, silazane groups are preferred because of their high reactivity with inorganic particles (C) (in the case of silica particles). In addition, those having a silazane group as a hydrolyzable group can be easily obtained by adding (Y n -Si-) structures.

[0141] Specific examples of the silane coupling agent (D) represented by the above formula (4) include, for example, alkoxysilanes such as methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, and decyltrimethoxysilane; chlorosilanes such as methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, and phenyltrichlorosilane; and hexamethyldisilazane, which have a hydrophobic group as a functional group. Examples of the silane having a vinyl group include alkoxysilanes such as methacryloxypropyltriethoxysilane, methacryloxypropyltrimethoxysilane, methacryloxypropylmethyldiethoxysilane, methacryloxypropylmethyldimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, and vinylmethyldimethoxysilane; chlorosilanes such as vinyltrichlorosilane and vinylmethyldichlorosilane; and divinyltetramethyldisilazane. Among these, taking into consideration the above description, it is particularly preferable that the silane having a hydrophobic group is hexamethyldisilazane, and the silane having a vinyl group is divinyltetramethyldisilazane.

[0142] <<Platinum or platinum compounds (E)>> The silicone rubber composition of this embodiment may contain platinum or a platinum compound (E). Platinum or a platinum compound (E) is a catalytic component that acts as a catalyst during curing. The amount of platinum or a platinum compound (E) added is a catalytic amount.

[0143] As the platinum or platinum compound (E), known substances can be used, such as platinum black, platinum supported on silica or carbon black, chloroplatinic acid or an alcohol solution of chloroplatinic acid, a complex salt of chloroplatinic acid and an olefin, and a complex salt of chloroplatinic acid and a vinylsiloxane.

[0144] The platinum or platinum compound (E) may be used alone or in combination of two or more kinds.

[0145] <<Water(F)>> Furthermore, the silicone rubber composition of the present embodiment may contain water (F) in addition to the above components (A) to (E).

[0146] Water (F) functions as a dispersion medium to disperse each component contained in the silicone rubber composition, and is also a component that contributes to the reaction between the inorganic particles (C) and the silane coupling agent (D). Therefore, the inorganic particles (C) and the silane coupling agent (D) can be more reliably bonded to each other in the silicone rubber, and uniform properties can be exhibited overall.

[0147] Furthermore, the silicone rubber composition of the present embodiment may contain, in addition to the above components (A) to (F), known additive components that are blended into silicone rubber compositions, such as dispersants, pigments, dyes, antistatic agents, antioxidants, flame retardants, and thermal conductivity improvers.

[0148] In the silicone rubber composition, the content ratio of each component is not particularly limited, but is set, for example, as follows.

[0149] In this embodiment, the upper limit of the content of the inorganic particles (C) may be, for example, 60 parts by weight or less, preferably 50 parts by weight or less, and more preferably 40 parts by weight or less, based on 100 parts by weight of the total amount of the vinyl group-containing organopolysiloxane (A). This improves the mechanical strength, such as the hardness and tear strength, of the release film 10, and improves the balance of the releasability, mold followability, and dimensional stability. The lower limit of the content of the inorganic particles (C) is not particularly limited, based on 100 parts by weight of the total amount of the vinyl group-containing organopolysiloxane (A), but may be, for example, 10 parts by weight or more.

[0150] The silane coupling agent (D) is preferably contained in an amount of 5 to 100 parts by weight, more preferably 5 to 40 parts by weight, per 100 parts by weight of the vinyl group-containing organopolysiloxane (A), which ensures that the dispersibility of the inorganic particles (C) in the silicone rubber composition is improved.

[0151] The content of the organohydrogenpolysiloxane (B) is preferably, for example, 0.5 parts by weight or more and 20 parts by weight or less, and more preferably 0.8 parts by weight or more and 15 parts by weight or less, relative to 100 parts by weight of the total amount of the vinyl group-containing organopolysiloxane (A), the inorganic particles (C), and the silane coupling agent (D). By keeping the content of (B) within the above range, a more effective curing reaction may be achieved.

[0152] The content of platinum or platinum compound (E) means a catalytic amount and can be appropriately set, but specifically, the platinum group metal in this component is 0.01 to 1000 ppm by weight, preferably 0.1 to 500 ppm, relative to the total amount of vinyl group-containing organopolysiloxane (A), inorganic particles (C), and silane coupling agent (D). By making the content of platinum or platinum compound (E) equal to or more than the lower limit, the obtained silicone rubber composition can be sufficiently cured. By making the content of platinum or platinum compound (E) equal to or less than the upper limit, the curing speed of the obtained release layer 1 can be improved.

[0153] Furthermore, when water (F) is contained, its content can be appropriately set, but specifically, for example, it is preferably in the range of 10 to 100 parts by weight, more preferably in the range of 30 to 70 parts by weight, relative to 100 parts by weight of the silane coupling agent (D). This makes it possible to more reliably proceed with the reaction between the silane coupling agent (D) and the inorganic particles (C).

[0154] The silicone rubber composition of the present embodiment may be a paste containing the solvent (G). Examples of the solvent (G) include aliphatic hydrocarbons such as pentane, hexane, cyclohexane, heptane, methylcyclohexane, ethylcyclohexane, octane, decane, dodecane, and tetradecane; aromatic hydrocarbons such as benzene, toluene, ethylbenzene, xylene, trifluoromethylbenzene, and benzotrifluoride; ethers such as diethyl ether, diisopropyl ether, dibutyl ether, cyclopentyl methyl ether, cyclopentyl ethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, 1,4-dioxane, 1,3-dioxane, and tetrahydrofuran; haloalkanes such as dichloromethane, chloroform, 1,1-dichloroethane, 1,2-dichloroethane, 1,1,1-trichloroethane, and 1,1,2-trichloroethane; carboxylic acid amides such as N,N-dimethylformamide and N,N-dimethylacetamide; and sulfoxides such as dimethyl sulfoxide and diethyl sulfoxide. These may be used alone or in combination of two or more. The solvent used here may be appropriately selected from among solvents capable of uniformly dissolving or dispersing the components in the paste.

[0155] [Method of manufacturing the release layer] Next, a method for producing the release layer 1 of this embodiment will be described. In the method for producing the release layer 1 of this embodiment, the above-mentioned silicone rubber composition is prepared, and the silicone rubber composition is formed into a film, which is then cured, thereby obtaining the release layer 1. Details are provided below.

[0156] First, the components of the silicone rubber composition are mixed uniformly using any kneading device to prepare the silicone rubber composition.

[0157] [1] For example, a predetermined amount of vinyl group-containing organopolysiloxane (A), inorganic particles (C), and a silane coupling agent (D) are weighed out, and then kneaded using any kneading device to obtain a kneaded product containing these components (A), (C), and (D).

[0158] It is preferable to prepare this mixture by first kneading the vinyl-containing organopolysiloxane (A) with the silane coupling agent (D) and then kneading (mixing) the inorganic particles (C), which improves the dispersibility of the inorganic particles (C) in the vinyl-containing organopolysiloxane (A).

[0159] In addition, when obtaining this kneaded product, water (F) may be added to the kneaded product of the components (A), (C), and (D) as necessary, which allows the reaction between the silane coupling agent (D) and the inorganic particles (C) to proceed more reliably.

[0160] Furthermore, it is preferable that the kneading of each of the components (A), (C), and (D) is carried out through a first step of heating at a first temperature and a second step of heating at a second temperature. This allows the surface of the inorganic particles (C) to be surface-treated with the coupling agent (D) in the first step, and allows the by-products generated by the reaction between the inorganic particles (C) and the coupling agent (D) to be reliably removed from the kneaded product in the second step. Thereafter, the component (A) may be added to the kneaded product obtained as necessary, and further kneaded. This allows the compatibility of the components in the kneaded product to be improved.

[0161] The first temperature is preferably, for example, about 40 to 120° C., and more preferably, for example, about 60 to 90° C. The second temperature is preferably, for example, about 130 to 210° C., and more preferably, for example, about 160 to 180° C.

[0162] Moreover, the atmosphere in the first step is preferably an inert atmosphere such as a nitrogen atmosphere, and the atmosphere in the second step is preferably a reduced pressure atmosphere.

[0163] Furthermore, the time for the first step is, for example, preferably about 0.3 to 1.5 hours, and more preferably about 0.5 to 1.2 hours, and the time for the second step is, for example, preferably about 0.7 to 3.0 hours, and more preferably about 1.0 to 2.0 hours.

[0164] By setting the above conditions for the first and second steps, the above effects can be obtained more significantly.

[0165] [2] Next, the organohydrogenpolysiloxane (B) and platinum or a platinum compound (E) are weighed out in predetermined amounts, and then the components (B) and (E) are kneaded into the mixture prepared in the above step [1] using any kneading device to obtain a silicone rubber composition. The obtained silicone rubber composition may be a paste containing a solvent.

[0166] When mixing the components (B) and (E), it is preferable to first mix the mixture prepared in the above step [1] with the organohydrogenpolysiloxane (B), and then mix the mixture prepared in the above step [1] with platinum or a platinum compound (E), and then mix the mixtures together. This ensures that the components (A) to (E) are dispersed in the silicone rubber composition without causing the reaction between the vinyl group-containing organopolysiloxane (A) and the organohydrogenpolysiloxane (B) to proceed.

[0167] The temperature at which the components (B) and (E) are kneaded is, for example, preferably about 10 to 70°C, and more preferably about 25 to 30°C, as roll setting temperature.

[0168] Furthermore, the kneading time is, for example, preferably about 5 minutes to 1 hour, and more preferably about 10 to 40 minutes.

[0169] In the above steps [1] and [2], by setting the temperature within the above range, it is possible to more accurately prevent or inhibit the progress of the reaction between the vinyl group-containing organopolysiloxane (A) and the organohydrogenpolysiloxane (B). In addition, in the above steps [1] and [2], by setting the kneading time within the above range, it is possible to more reliably disperse the components (A) to (E) in the silicone rubber composition.

[0170] The kneading device used in each of steps [1] and [2] is not particularly limited, but for example, a kneader, a two-roll mill, a Banbury mixer (continuous kneader), a pressure kneader, etc. can be used.

[0171] In addition, a reaction inhibitor such as 1-ethynylcyclohexanol may be added to the kneaded mixture in step [2], which makes it possible to more effectively prevent or inhibit the progress of the reaction between the vinyl group-containing organopolysiloxane (A) and the organohydrogenpolysiloxane (B) even if the temperature of the kneaded mixture is set to a relatively high temperature.

[0172] [3] Next, the silicone rubber composition obtained in step [2] may be dissolved in a solvent to form a paste.

[0173] [4] Next, the silicone rubber composition is processed into a film and cured to form the release layer 1. Specifically, the silicone rubber composition is formed into a film by extrusion molding, calendar molding, press molding, coating, etc. During film formation, the surface shape of a roll or the like may be transferred or embossed.

[0174] In this embodiment, the curing step of the silicone rubber composition is carried out, for example, by heating at 100 to 250° C. for 1 to 30 minutes (first curing) and then post-baking at 100 to 250° C. for 1 to 4 hours (second curing).

[0175] Through the steps described above, the release layer 1 using the silicone rubber composition of the present embodiment, that is, the release film 10, is obtained.

[0176] [Uses and methods of use of release film] The release film 10 of this embodiment is used in a resin-encapsulating process of a semiconductor device, in which it is disposed between a mold to which an encapsulating resin is supplied and a semiconductor device to be encapsulated with resin. Hereinafter, an example of a method for manufacturing a resin-encapsulated semiconductor device using the release film 10 will be described. However, the use of the release film 10 is not limited to this. For example, it can be used as a release film when curing a prepreg of a thermosetting resin such as CFRP, a release film for molding a thermosetting resin, a transfer release film for decoration when printing or the like on a product having a three-dimensional shape, and the like.

[0177] The method for manufacturing a resin-encapsulated semiconductor device includes the following steps. (Step 1) Preparation of semiconductor device (Step 2) Release film installation process (Step 3) Sealing resin supply process (Step 4) Curing step (Step 5) Demolding of the molded body Each step will be described in detail below.

[0178] (Step 1) Preparation of semiconductor device The semiconductor device is formed by electrically connecting electrode pads on circuit wiring provided on a support and electrodes provided on a semiconductor element. Examples of the semiconductor element include optical elements such as a light emitting element and a light receiving element. An example of the light emitting element is an LED chip (light emitting diode), and an example of the light receiving element is an image sensor. The support is a substrate formed in any shape such as a circle or a polygon, etc. Examples of the support include a ceramic substrate, a silicone substrate, a metal substrate, a rigid substrate such as an epoxy resin or a BT resin, or a flexible substrate such as a polyimide resin or a polyethylene substrate.

[0179] (Step 2) Release film installation process The release film 10 is placed in a mold having a recess for supplying the sealing resin. At this time, the release surface 3 of the release film 10 is placed on the front side, that is, in such a way that it comes into contact with the sealing resin that will be supplied later. The release film 10 may also be disposed within the recess of the mold and along the surface of the flat portion surrounding the recess. At this time, it is preferable to use a suction device or the like to suck and discharge air, moisture, gas, etc. in the space between the release film 10 and the mold, so that the release film 10 conforms to the shape of the recess of the mold, and to perform vacuum adsorption. Furthermore, in order to firmly fix the release film 10 to the mold, the release film 10 may be clamped by a chuck mechanism disposed at a position corresponding to the outer periphery of the sealing resin injection area, the outer periphery of the entire release film 10, or the outer periphery of the entire mold. Examples of the mold include a known metal mold and a resin mold.

[0180] (Step 3) Sealing resin supply process Next, a sealing resin is supplied to the recess of the mold in the region where the release film 10 is disposed. A known method can be used as the supplying method. In addition, the sealing resin can be a known resin, for example, silicone-based resin, epoxy-based resin, acrylic-based resin, fluorine-based resin, polyimide-based resin, silicone-modified epoxy-based resin, etc., or a mixture of these, and precursors thereof. In this embodiment, when the release film 10 is applied to a compression molding method, the sealing resin is preferably processed into a tablet, granule, sealed particle, or sheet shape. In the mold, the sealing resin is heated to a predetermined temperature and is in a fluid state.

[0181] (Step 4) Curing step Next, the surface of the prepared semiconductor device on which the semiconductor element is provided is pressed against a mold in which a sealing resin is supplied into a recess. This causes the semiconductor element to be covered with the sealing resin. The sealing resin is then heated and pressurized to harden, thereby obtaining a molded body. When the sealing resin is a precursor of a curable resin, it may be cured by heating and irradiation with active energy rays, examples of which include radiation, ultraviolet rays, visible light, and electron beams.

[0182] (Step 5) Demolding of the molded body The molded body is then removed from the mold. In the mold-removing process, air, moisture, gas, etc. are supplied between the release film 10 and the mold, so that the release film 10 is peeled off from the mold and the molded body is removed. At the same time or after this, the release film 10 is released from the molded body. When there is one semiconductor element provided on the support, this molded body becomes a resin-sealed semiconductor device.

[0183] <Second embodiment> In the first embodiment, the release film 10 is described as being composed of the release layer 1, but in the second embodiment, an example will be described in which the release film 11 has a structure in which the release layer 1 and the base layer 2 are laminated together. In the following, a description of the same structure and effects as those in the first embodiment will be omitted.

[0184] FIG. 2 is a cross-sectional view that diagrammatically illustrates a cross section of a release film of a second embodiment. As shown in FIG. 2, the release film 11 of this embodiment includes a base layer 2 and a release layer 1 laminated on the base layer 2.

[0185] The thickness of the release film 11 is preferably 25 μm or more and 150 μm or less, more preferably 35 μm or more and 100 μm or less, and even more preferably 40 μm or more and 50 μm or less.

[0186] [Base material layer] The base layer 2 is used from the viewpoint of imparting an appropriate rigidity to the release film 11.

[0187] The thickness of the base layer 2 is preferably 5 μm or more and 50 μm or less, more preferably 9 μm or more and 35 μm or less, and even more preferably 12 μm or more and 25 μm or less. By setting the thickness of the base layer 2 to the above-mentioned lower limit or more, the rigidity of the release film 11 is increased, and it becomes easier to suppress excessive deformation and wrinkles. As a result, mold followability and dimensional stability are obtained. On the other hand, by setting the thickness of the base layer 2 to the above-mentioned upper limit or less, the rigidity of the release film 11 can be controlled, and a good balance between mold followability and releasability can be achieved.

[0188] The material of the base layer 2 may be one or more selected from the group consisting of polyester resin, poly-4-methyl-1-pentene resin, polyamide resin, and polypropylene resin. Examples of the polyester resin include polyethylene terephthalate resin (PET), polybutylene terephthalate resin (PBT), polytrimethylene terephthalate resin (PTT), polyhexamethylene terephthalate resin (PHT), and polyethylene naphthalate resin (PEN). Examples of the polyamide resin include aliphatic polyamides, aromatic polyamides, etc. Specific examples of the aliphatic polyamides include polyamide 6, polyamide 6,6, polyamide 6-6,6 copolymer, polyamide 11, polyamide 12, etc. Specific examples of the aromatic polyamides include polyamide 61, polyamide 66 / 6T, polyamide 6T / 6, polyamide 12 / 6T, etc. Among these, polyethylene terephthalate resin, polybutylene terephthalate resin, and polyamide resin are preferable.

[0189] Alternatively, a stretched film may be used as the base layer 2, and the stretching may be carried out by using a known method such as sequential biaxial stretching, simultaneous biaxial stretching, or tubular stretching.

[0190] [Release film manufacturing method] The release film 11 can be produced by a known method such as co-extrusion, extrusion lamination, dry lamination, inflation, etc. The release layer 1 may be formed on the base layer 2 by applying a silicone rubber composition prepared in a paste form to the surface of the base layer 2. In the release film 11 of the second embodiment, for example, the release layer 1 and the base layer 2 may be produced separately and then bonded together by a laminator, etc. In addition, the release layer 1 and the base layer 2 may be bonded together as they are, or may be bonded together via an adhesive layer. The method for producing the base layer 2 is not limited, and specific examples include an inflation extrusion method and a T-die extrusion method. In the second embodiment, the silicone rubber composition, paste, and film-like cured product of the silicone rubber composition described in the first embodiment can be used.

[0191] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES

[0192] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.

[0193] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.

[0194] (1) Raw materials The raw material components used in the examples and comparative examples shown in Table 1 are shown below. (Vinyl-containing organopolysiloxane (A)) Low vinyl group-containing linear organopolysiloxane (A1-1): Vinyl group-containing dimethylpolysiloxane (structure represented by formula (1-1) and R 1 (Structure in which only the terminal is vinyl) High vinyl group-containing linear organopolysiloxane (A1-2): Vinyl group-containing dimethylpolysiloxane (structure represented by formula (1-1) and R 1 and R2 is a vinyl group) Low vinyl group-containing linear organopolysiloxane (A1-3): Vinyl group-containing dimethylpolysiloxane (structure represented by formula (1-1) and R 1 and R 2 is a vinyl group)

[0195] (Organohydrogenpolysiloxane (B)) Momentive: "TC-25D"

[0196] (Inorganic particles (C)) Silica particles (C-1): Silica particles (particle size 7 nm, specific surface area 300 m 2 / g), manufactured by Nippon Aerosil Co., Ltd., "AEROSIL300" Silica particles (C-2): Silica microparticles (particle size 7 nm, specific surface area 240 m2 / g), manufactured by Nippon Aerosil Co., Ltd., "AEROSIL R976"

[0197] (Silane coupling agent (D)) Silane coupling agent (D-1): Hexamethyldisilazane (HMDZ), manufactured by Gelest, "HEXAMETHYLDISILAZANE (SIH6110.1)" Silane coupling agent (D-2): Divinyltetramethyldisilazane, manufactured by Gelest, "1,3-DIVINYLTETRAMETHYLDISILAZANE (SID4612.0)"

[0198] (Platinum or platinum compounds (E)) Momentive: "TC-25A"

[0199] (Synthesis of vinyl group-containing organopolysiloxane (A)) [Synthesis Scheme 1: Synthesis of low vinyl group-containing linear organopolysiloxane (A1-1)] A low-vinyl-group-containing linear organopolysiloxane (A1-1) was synthesized according to the following formula (5). That is, 74.7 g (252 mmol) of octamethylcyclotetrasiloxane and 0.1 g of potassium siliconate were placed in a 300 mL separable flask equipped with a cooling tube and stirring blade and replaced with Ar gas, and the temperature was raised and the mixture was stirred at 120° C. for 30 minutes. At this time, an increase in viscosity was confirmed. The mixture was then heated to 155° C. and stirred for 3 hours, after which 0.1 g (0.6 mmol) of 1,3-divinyltetramethyldisiloxane was added and the mixture was stirred at 155° C. for an additional 4 hours. After four hours, the mixture was diluted with 250 mL of toluene and then washed three times with water. The washed organic layer was washed several times with 1.5 L of methanol for reprecipitation purification, and the oligomer and polymer were separated. The resulting polymer was dried overnight at 60°C under reduced pressure to obtain a low-vinyl-group-containing linear organopolysiloxane (A1-1) (Mn = 2.2 × 10 5 , Mw=4.8×10 5 The vinyl group content calculated from H-NMR spectrum measurement was 0.04 mol %.

[0200] [ka]

[0201] [Synthesis Scheme 2: Synthesis of high vinyl group-containing linear organopolysiloxane (A1-2)] A highly vinyl-containing linear organopolysiloxane (A1-2) was synthesized as shown in formula (6) below by the same synthesis process as for (A1-1), except that 0.86 g (2.5 mmol) of 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane was used in addition to 74.7 g (252 mmol) of octamethylcyclotetrasiloxane in the synthesis process for (A1-1) above. (Mn=2.3×10 5 , Mw=5.0×10 5 The vinyl group content calculated from H-NMR spectrum measurement was 0.93 mol %. [ka]

[0202] [Synthesis Scheme 3: Synthesis of low vinyl group-containing linear organopolysiloxane (A1-3)] In the synthesis process of (A1-2) above, 75.3 g (254 mmol) of octamethylcyclotetrasiloxane and 0.12 g (0.35 mmol) of 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane were used, and the stirring time after heating to 155°C was changed to 3 hours. The same synthesis process as that of (A1-2) was repeated to synthesize a low vinyl group-containing linear organopolysiloxane (A1-3) as shown in the above formula (6). (Mn=2.5×10 5 , Mw=5.0×10 5 The vinyl group content calculated from H-NMR spectrum measurement was 0.13 mol %.

[0203] (2) Preparation of Silicone Rubber Composition A silicone rubber composition was prepared as follows. First, a mixture of 90% vinyl group-containing organopolysiloxane (A), silane coupling agent (D), and water (F) was pre-kneaded in the proportions shown in Table 1 below, and then inorganic particles (C) were added to the mixture and further kneaded to obtain a kneaded product (silicone rubber compound). Here, the kneading after the addition of the inorganic particles (C) was carried out through a first step of kneading for 1 hour under conditions of 60 to 90°C in a nitrogen atmosphere for the coupling reaction, and a second step of kneading for 2 hours under conditions of 160 to 180°C in a reduced pressure atmosphere for the removal of the by-product (ammonia). Thereafter, the mixture was cooled, and the remaining 10% of the vinyl group-containing organopolysiloxane (A) was added in two portions and kneaded for 20 minutes. Next, organohydrogenpolysiloxane (B) (TC-25D) and platinum or platinum compound (E) (TC-25A) were added in the ratios shown in Table 1 below to 100 parts by weight of the resulting kneaded product (silicone rubber compound), and the mixture was kneaded with a roll to obtain a silicone rubber composition.

[0204] [Table 1]

[0205] (3) Measurement of physical properties of silicone rubber composition The physical properties of the silicone rubber composition were measured according to the following procedures, and the results are shown in Table 2.

[0206] ·Tear strength TS0 (Measuring procedure for tear strength) A crescent-shaped test piece was prepared from the cured product of the silicone rubber composition in accordance with JIS K6252 (2001), and the tear strength of the obtained crescent-shaped test piece was measured at 25° C. The unit is N / mm.

[0207] ·Tear strength TS1 (N / mm) (Measuring procedure for tear strength) A crescent-shaped test piece was prepared in accordance with JIS K6252 (2001) using the cured product of the silicone rubber composition, and then the test piece was held at 100°C for 30 minutes. The tear strength of the crescent-shaped test piece obtained at 100°C was determined as TS1 (N / mm).

[0208] ·Tear strength TS2 (N / mm) (Measuring procedure for tear strength) A crescent-shaped test piece was prepared in accordance with JIS K6252 (2001) using the cured product of the silicone rubber composition, and then the test piece was held at 150°C for 30 minutes. The tear strength of the crescent-shaped test piece obtained at 150°C was determined as TS2 (N / mm).

[0209] Breaking elongation BE0s(%) (Procedure for measuring breaking elongation) Using the cured product of the silicone rubber composition, dumbbell-shaped No. 3 test pieces were prepared in accordance with JIS K6251 (2004), and the breaking elongation of the resulting dumbbell-shaped No. 3 test pieces was measured at 25°C. The breaking elongation was calculated as [gauge line movement distance (mm)] ÷ [initial gauge line distance (20 mm)] × 100, and was designated as BE0s. The unit is %.

[0210] Breaking elongation BE0(%) (Procedure for measuring breaking elongation) Using the cured product of the silicone rubber composition, dumbbell-shaped No. 3 test pieces are prepared in accordance with JIS K6251 (2004), and the breaking elongation of the resulting dumbbell-shaped No. 3 test pieces is measured at 25°C. The breaking elongation is calculated as [chuck movement distance (mm)] ÷ [initial chuck distance (60 mm)] × 100, and is designated as BE0. The unit is %.

[0211] Breaking elongation BE1 (%) (Procedure for measuring breaking elongation) Using the cured product of the silicone rubber composition, dumbbell-shaped No. 3 test pieces were prepared in accordance with JIS K6251 (2004), and after holding at 100°C for 30 minutes, the breaking elongation of the resulting dumbbell-shaped No. 3 test pieces at 100°C was measured. The breaking elongation was calculated as [chuck movement distance (mm)] ÷ [initial chuck distance (60 mm)] × 100, and was designated as BE1. The unit is %.

[0212] Breaking elongation BE2 (%) (Procedure for measuring breaking elongation) Using the cured product of the silicone rubber composition, dumbbell-shaped No. 3 test pieces were prepared in accordance with JIS K6251 (2004), and after holding at 150°C for 30 minutes, the breaking elongation of the resulting dumbbell-shaped No. 3 test pieces at 150°C was measured. The breaking elongation was calculated as [chuck movement distance (mm)] ÷ [initial chuck distance (60 mm)] × 100, and was designated as BE2. The unit is %.

[0213] Elongation at 1MPa E1 (%) (Procedure for measuring elongation at 1 MPa) Using the cured product of the silicone rubber composition, dumbbell-shaped No. 3 test pieces were prepared in accordance with JIS K6251 (2004), and tensile tests were conducted at 25°C and a tensile speed of 500 mm / min. The elongation of the resulting dumbbell-shaped No. 3 test piece when the stress reached 1 MPa was calculated as E1 using the formula [gauge line movement distance (mm)] ÷ [initial gauge line distance (20 mm)] × 100. The unit is %.

[0214] Elongation at 0.2MPa E2 (%) (Procedure for measuring elongation at 0.2 MPa) Using the cured product of the silicone rubber-based curable composition, a dumbbell-shaped No. 3 test piece was prepared in accordance with JIS K6251 (2004), and a tensile test was carried out at 25°C at a tensile speed of 500 mm / min. The elongation of the resulting dumbbell-shaped No. 3 test piece when the stress reached 0.2 MPa was calculated using the formula [gauge line movement distance (mm)] ÷ [initial gauge line distance (20 mm)] × 100. The unit is %.

[0215] Tensile strength S (MPa) (Procedure for measuring tensile strength) Using the cured product of the silicone rubber composition, dumbbell-shaped No. 3 test pieces were prepared in accordance with JIS K6251 (2004), and the tensile strength of the dumbbell-shaped No. 3 test pieces at 25° C. was measured (units are MPa).

[0216] Stroke change rate after n hours SCn(%) (Procedure for measuring stroke change rate) Dumbbell-shaped No. 3 test pieces were prepared in accordance with JIS K6251 (2004) using the cured product of the silicone rubber composition, and the elongation of the resulting dumbbell-shaped No. 3 test pieces was measured over time at 25°C when held between the chucks at a stress of 1 MPa. The time when the stress became 1 MPa was defined as 0h, and the stroke amount after a certain time n (h) was defined as En (%) = [chuck movement distance (mm)] ÷ [initial chuck distance (60 mm)] × 100. The stroke change rate was calculated from the measured stroke amount En based on the following formula. Stroke change rate after n hours SCn (%) = (En-E0) / E0 x 100

[0217] Durometer hardness A (Durometer hardness A measurement procedure) A sheet-like test specimen was prepared using the cured product of the silicone rubber composition, and the durometer hardness A of the resulting sheet-like test specimen at 25° C. was measured in accordance with JIS K6253 (1997).

[0218] Plasticity (Procedure for measuring plasticity) The uncured silicone rubber composition was used as a test sample, and the plasticity of the resulting test sample was measured at 25° C. 10 minutes after the start of the measurement using a Williams plasticity meter in accordance with JIS K6249 (2003).

[0219] (4) Preparation of release layer (release film) <Example 1> [Creating a release film with only a release layer] The silicone rubber composition prepared in (3) above was pressed at 160°C and 20 MPa for 20 minutes to form a film having a thickness of 300 μm and was cured primarily. It was then heated at 200°C for 4 hours to be cured secondary, producing a release film consisting of a release layer. In addition, during this procedure, the unevenness of the mold surface was transferred when the silicone rubber composition was pressed, thereby performing uneven processing. The release layer of the obtained release film had a thickness of 300 μm, and the surface roughness Rz of the release surface of the release layer was 3 μm.

[0220] <Example 2> [Preparation of release film with base layer] A biaxially oriented polyethylene terephthalate film (Toyobo Co., Ltd., Toyobo Ester (registered trademark) film, 12 μm thick) was used as a base layer, and a paste (solid content 25 mass %, decane solvent) made of the silicone rubber composition prepared in (3) above was applied onto the base layer using a bar coater and cured at 180°C for 120 minutes to obtain a release film having a release layer on the base layer. In this procedure, after the paste made of the silicone rubber composition was dried, a matte film was sandwiched between the two layers to provide an uneven surface to the release layer. The release layer of the obtained release film had a thickness of 38 μm, and the surface roughness Rz of the release surface of the release layer was 2 μm.

[0221] <Comparative Example 1> A biaxially oriented polyethylene terephthalate film (Toyobo Co., Ltd., Toyobo Ester (registered trademark) film, 12 μm thick) was used as a base layer, and a paste (solid content 25 mass %, decane solvent) made of the silicone rubber composition prepared in (3) above was applied onto the base layer using a bar coater and cured at 180°C for 120 minutes to obtain a release film having a release layer on the base layer. In this procedure, after the paste made of the silicone rubber composition was dried, a matte film was sandwiched between the two layers to provide an uneven surface to the release layer. The release layer of the obtained release film had a thickness of 38 μm, and the surface roughness Rz of the release surface of the release layer was 2 μm.

[0222] (5) Measurement and evaluation The following measurements and evaluations were carried out using the obtained release film. The results are shown in Table 2.

[0223] (i) Measurement of the surface roughness Rz of the release surface of the release layer Measurements were performed in accordance with JIS B0601:2013.

[0224] (ii) Evaluation of mold conformability, dimensional stability, and releasability First, a tablet of the following thermosetting resin composition was prepared as a sealing resin. (raw materials) Epoxy resin 1: Biphenyl aralkyl type epoxy resin (manufactured by Nippon Kayaku Co., Ltd., NC-3000) Epoxy resin 2: Biphenyl type epoxy resin (Mitsubishi Chemical, YL6677) Hardener 1: Phenol aralkyl resin containing biphenylene skeleton (manufactured by Nippon Kayaku Co., Ltd., GPH-65) Hardener 2: Triphenylmethane type phenolic resin modified with formaldehyde (Air Water Corporation, HE910-20) Curing accelerator: Triphenylphosphine (Hokko Chemical Industry Co., Ltd., TPP) Inorganic filler: Fused spherical silica (Denki Kagaku Kogyosha, FB-950FC) Colorant: Carbon black (Mitsubishi Chemical, MA-600) Coupling agent: N-phenyl-γ-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-573) Release agent: Carnauba wax (Nikko Fine Co., Ltd., Nikko Carnauba) (procedure) The above-mentioned epoxy resin 1 was prepared in an amount of 4.5 parts by mass, epoxy resin 2 in an amount of 4.5 parts by mass, curing agent 1 in an amount of 2.8 parts by mass, curing agent 2 in an amount of 2.8 parts by mass, curing accelerator in an amount of 0.4 parts by mass, inorganic filler in an amount of 84.2 parts by mass, colorant in an amount of 0.2 parts by mass, coupling agent in an amount of 0.4 parts by mass, and release agent in an amount of 0.2 parts by mass. Next, the raw material components were mixed at room temperature using a mixer, and then roll-kneaded while being heated with two rolls at 45 ° C. and 90 ° C. to obtain a kneaded product. Next, the kneaded product was cooled and then pulverized to obtain a pulverized product. Next, the pulverized product was tableted to obtain a tablet-shaped thermosetting resin composition.

[0225] Next, using each release film, the thermosetting resin composition was cured (resin sealing) according to the following procedure. First, a COSMO-TFlex Series manufactured by Asahi Engineering Co., Ltd. was used as a hybrid molding machine for transfer molding and compression molding. First, each release film of the examples and comparative examples was placed inside a mold equipped in a molding machine, and the space inside the mold was evacuated to a vacuum, thereby allowing the release film to conform to the mold. Next, a tablet of the thermosetting resin composition was placed in a predetermined position. Then, the mold of the molding machine was clamped at a clamping pressure of 300 kg / cm. 2 After tightening the mold under the condition of 1.0 mm, the above-mentioned thermosetting resin composition in a molten state was injected at a pressure of 80 kg / cm 2 The thermosetting resin composition was poured into the inner space of the mold of the molding machine under the condition of 6 kg / cm. The cavity of the mold was then moved to a position where the thermosetting resin composition was poured into the inner space of the mold of the molding machine under the condition of 6 kg / cm. 2The mixture was molded for 2 minutes at 175° C. while being pressed at a pressure of 1.0 kPa. Thereafter, the upper and lower dies were opened to release the cured product of the thermosetting resin composition from the release film.

[0226] [Mold followability] In the above procedure, the degree of air entrapment between the release film and the four corners of the mold when the release film was made to follow the mold by vacuum drawing was evaluated according to the following criteria. ◎: No air pockets ○: There are small air pockets, but no practical problems △: There was a small air pocket, which reduced the degree of vacuum for film adsorption. ×: Large air pockets cause poor tracking (or evaluation is impossible)

[0227] [Dimensional stability] In the above procedure, the appearance (wrinkles, etc.) of the cured product after it was released from the release film after molding was evaluated according to the following criteria. 〇: No wrinkles or deformations, no problems △: There are some wrinkles, but no problem in use ×: Large wrinkles and molding defects occurred

[0228] [Mold releasability] In the above procedure, the release behavior when the cured product was released from the release film after molding and the state of the cured product (displacement, bending, etc.) were evaluated according to the following criteria. 〇: No problems with demolding or molded products △: The molded product shifts or bends when released from the mold, but this does not pose a problem in practical use. ×: Unable to release from mold, or large wrinkles were transferred to the cured product

[0229] [Table 2] [Explanation of symbols]

[0230] 1 Release layer 2 Base material layer 3 Release surface 10 Release film 11 Release film

Claims

1. A release film in which a layer constituting at least one surface thereof is made of a cured product of a silicone rubber composition, the silicone rubber composition comprises a vinyl group-containing organopolysiloxane, an organohydrogenpolysiloxane, inorganic particles, and a silane coupling agent; When the tear strength of the cured product of the silicone rubber composition is TS0 (N / mm) and the elongation at break is BE0s (%), the following properties are obtained: 2.4 x 10 4 ≦TS0×BE0s is satisfied, The surface roughness Rz of the one surface of the release film is 0.1 to 3 μm. (Procedure for measuring tear strength) A crescent-shaped test piece is prepared from the cured product of the silicone rubber composition in accordance with JIS K6252 (2001), and the tear strength of the obtained crescent-shaped test piece at 25° C. is measured and designated as TS0, expressed in N / mm. (Procedure for measuring elongation at break) A dumbbell-shaped No. 3 test piece is prepared using the cured product of the silicone rubber composition in accordance with JIS K6251 (2004), and the breaking elongation of the resulting dumbbell-shaped No. 3 test piece is measured at 25° C. The breaking elongation is calculated as [gauge line movement distance (mm)]÷[initial gauge line distance (20 mm)]×100, and is designated as BE0s, and is expressed in %.

2. When the tensile strength of the cured product of the silicone rubber composition is S (MPa), which is measured by the following procedure, 1.4 x 10 5 The release film according to claim 1 , which satisfies ≦TS0×BE0s×S. (Procedure for measuring tensile strength) A dumbbell-shaped No. 3 test piece is prepared using the cured product of the silicone rubber composition in accordance with JIS K6251 (2004), and the tensile strength of the dumbbell-shaped No. 3 test piece at 25° C. is measured and represented as S. The unit is MPa.

3. A release film in which a layer constituting at least one surface thereof is made of a cured product of a silicone rubber composition, the silicone rubber composition comprises a vinyl group-containing organopolysiloxane, an organohydrogenpolysiloxane, inorganic particles, and a silane coupling agent; When the tear strength of the cured product of the silicone rubber composition, measured by the following procedure, is TS0 (N / mm) and TS1 (N / mm), ((TS1-TS0) / TS0) x 100 is -85% or more and 5% or less, The surface roughness Rz of the one surface of the release film is 0.1 to 3 μm. (Procedure for measuring tear strength) A crescent-shaped test piece is prepared in accordance with JIS K6252 (2001) using the cured product of the silicone rubber composition, and the tear strength of the obtained crescent-shaped test piece at 25° C. is designated as TS0 (N / mm). A crescent-shaped test piece is prepared in accordance with JIS K6252 (2001) using the cured product of the silicone rubber composition, and then the test piece is held at 100°C for 30 minutes. The tear strength of the crescent-shaped test piece obtained at 100°C is defined as TS1 (N / mm).

4. When the tear strength of the cured product of the silicone rubber composition is TS2 (N / mm), which is measured by the following procedure, The release film according to claim 3, wherein ((TS2-TS0) / TS0) x 100 is -88% or more and 5% or less. (Procedure for measuring tear strength) A crescent-shaped test piece is prepared in accordance with JIS K6252 (2001) using the cured product of the silicone rubber composition, and then the test piece is held at 150°C for 30 minutes. The tear strength of the crescent-shaped test piece obtained at 150°C is defined as TS2 (N / mm).

5. 5. The release film according to claim 1, wherein the durometer hardness A of a cured product of the silicone rubber composition is 20 or more and 80 or less, as measured by the following procedure. (Procedure for measuring durometer hardness A) A sheet-like test specimen is prepared using the cured product of the silicone rubber composition, and the durometer hardness A of the resulting sheet-like test specimen at 25° C. is measured in accordance with JIS K6253 (1997).

6. When the elongation of the cured product of the silicone rubber composition at 1 MPa is defined as E1 (%), which is measured by the following procedure, The release film according to claim 1 , wherein 15≦E1 and 20≦TS0 are satisfied. (Procedure for measuring elongation at 1 MPa) A dumbbell-shaped No. 3 test piece was prepared using the cured product of the silicone rubber composition in accordance with JIS K6251 (2004), and a tensile test was conducted at 25°C at a tensile speed of 500 mm / min, and the elongation of the resulting dumbbell-shaped No. 3 test piece when the stress reached 1 MPa was calculated using the formula [gauge line movement distance (mm)]÷[initial gauge line distance (20 mm)]×100, and designated as E1. The unit is %.

7. When the stroke change rate after 1 hour of the cured product of the silicone rubber composition is measured by the following procedure and defined as SC1 (%), The release film according to claim 1 , wherein SC1≦50 and TS0 are satisfied. (Procedure for measuring stroke change rate) A dumbbell-shaped No. 3 test piece is prepared in accordance with JIS K6251 (2004) using the cured product of the silicone rubber composition, and the elongation of the resulting dumbbell-shaped No. 3 test piece is measured over time at 25°C when held between chucks at a stress of 1 MPa. The time when the stress becomes 1 MPa is defined as 0 h, and the stroke amount after a predetermined time n (h) is defined as En (%) = [chuck movement distance (mm)] ÷ [initial chuck distance (60 mm)] × 100. The stroke change rate is calculated from the measured stroke amount En based on the following formula. Stroke change rate after n hours SCn (%) = (En-E0) / E0 x 100 The stroke change rate when n=1 is defined as SC1 (%).

8. The surface free energy of the one surface is 10 mJ / m 2 20mJ / m or more 2 The release film according to claim 1 , wherein:

9. A release film according to claim 1, wherein the content of the inorganic particles is 10 to 60 parts by weight per 100 parts by weight of the vinyl group-containing organopolysiloxane.

10. The release film according to any one of claims 1 to 9, wherein the inorganic particles are particles made using one or more types selected from the group consisting of calcium carbonate, zinc oxide, alumina, crystalline silica, amorphous silica, fused silica, and zeolite.

11. The release film according to claim 1 , which is constituted by a layer made of a cured product of the silicone rubber composition.

12. The release film according to claim 1 , wherein the release film has a structure in which a base layer and a layer made of a cured product of the silicone rubber composition are laminated together.

13. The release film according to claim 12, wherein the base layer is one or more resins selected from the group consisting of polyester resin, poly 4-methyl 1-pentene resin, polyamide resin, and polypropylene resin.

14. The release film according to claim 1 , which is intended to be disposed between a mold to which a sealing resin is supplied and a semiconductor device to be resin-encapsulated in a resin-encapsulating process of a semiconductor device.

Citation Information

Patent Citations

  • Optical device and manufacturing method of producing the same

    JP2010245477A

  • Molded product

    JP2019199508A